The alternative splicing regulator Tra2b is required for somitogenesis and regulates splicing of an inhibitory Wnt11b isoform - Dichmann, Darwin S (Cell Rep, 2015)
Alternative splicing is pervasive in vertebrates, yet little is known about most isoforms or their regulation. transformer-2b (tra2b) encodes a splicing regulator whose endogenous function is poorly understood. Tra2b knockdown in Xenopus results in embryos with multiple defects, including defective somitogenesis. Using RNA-seq, we identify 142 splice changes, mostly intron retention and exon skipping, of which 89% are not in current annotations. A previously not described isoform of wnt11b retains the last intron, resulting in a truncated ligand (Wnt11b-short). We show that this isoform acts as a dominant-negative in cardiac gene induction and pronephric tubule formation. To determine the contribution of Wnt11b-short to the tra2b phenotype, we induce retention of intron4 in wnt11b, which recapitulates the failure to form somites but not other tra2b morphant defects. This alternative splicing of a Wnt ligand adds intricacy to a complex signaling pathway and highlights intron retention as a regulatory mechanism.